Analysis of the leading fisheries sector in the minapolitan area of Pangkep Regency, South Sulawesi Province - Malik Malik; Rosnida Rosnida; Andi Nur Apung Massiseng (Sekolah Tinggi Ilmu Pertanian Wuna, 2022)
The purpose of this study was to determine the existing condition of the minapolitan area in Pangkep district and to determine the leading sector of capture fisheries and aquaculture commodities in the minapolitan area of Pangkep District, South Sulawesi Province. Data collection techniques were carried out using observation, interviews using questionnaires and documentation. The type of data collected is primary data, namely observation data regarding facilities supporting fishery activities in the Minapolitan area, interview data for respondents from fisheries business actors or fisheries households regarding fishery activities and demographics, then secondary data from agencies related to the production of fishery commodities in Pangkep Regency. And South Sulawesi. This research was conducted in the minapolitan area of Pangkep Regency, South Sulawesi Province, in February – April 2021. The results showed that the existing condition in the availability of infrastructure facilities in the minapolitan area in the mainland area of Pangkep Regency, especially at the level of availability of facilities, was categorized as medium. Supporting facilities for fishery activities are at an availability level of 61.6 per cent because many are abandoned due to not being able to optimize their operations. The leading fishery commodities in the Minapolitan area that have the export potential are Tilapia, Patin, Cottonii seaweed and Milkfish. Fishery commodities that have the potential to meet local market demand are Vanamei Shrimp and Windu Shrimp. Fishery commodities that are not superior are Gracillaria Seaweed, Carp, Catfish and Crayfish.